Simple and choice response time elite and novice karate athletes and non-athlete - Liu, Y.; See, L.; Chang, S.; Lee, J.; Shieh, L.; Ning, Y.; Lim, A. Y.; Chen, W. (Archives of Budo, 2018)
Background and Study Aim: Simple and choice response time (RT) are important determinants for karate competition. Studies showed notable controversy on a discrepancy in RT among different level of karate skill. This study`s aim is knowledge about simple and choice RT elite and novice karate athletes and also non-athletes (all from college students).